Development of Smart Book-Based Augmented Reality Learning Media to Improve Student Learning Outcomes of Human Respiratory System Materials - Ghina Syakirah; Aldina Eka Andriani (JURNAL PENDIDIKAN MIPA, 2026)
The limited availability of learning media capable of concretely visualizing objects has resulted in low student learning outcomes regarding the human respiratory system. This study aims to describe the design and development, test the feasibility, and evaluate the effectiveness of smart book-based augmented reality learning media to improve the learning outcomes of fifth-grade students at SDN Wonolopo 02 in Semarang. This is an R&D study using the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The research subjects consisted of 28 fifth-grade students. Non-test data collection techniques included observation, interviews, and documentation, as well as questionnaires and tests, such as pre-tests and post-tests. Data analysis utilized normality tests, paired-sample t-tests, and N-Gain tests. The results showed that the media was developed using Assembler Edu which was integrated with a smart book to display 3D interactively and equipped with a learning stimulus. The feasibility of the media was shown by the validation of the material experts of 93.75%, the media experts 93% of the very feasible category and the teacher's response of 96.66%, the response of 93.45% of the students in the very feasible category. The effectiveness of the media was shown by an increase in learning outcomes of 20.32%, the significance value of the paired sample t-test was 0.000 (<0.05), and the average value of N-Gain was 0.5206 in the medium category. In conclusion, smart book-based augmented reality learning media has been successfully developed, very feasible and effective in improving the learning outcomes of grade V students of SDN Wonolopo 02.